Relaxation Therapy on The Level of Anxiety of Post Sectio Caesarea: A Literature Review - Pryati Rihi; Muflihatul Muniroh; Dwi Susilawati (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Anxiety can be overcome by non-pharmacological anxiety management, for example by relaxation therapy, which is a therapy that is often used to overcome anxiety or negative emotions using various types of relaxation. The purpose of this literature review is to examine the results of the past 10 years of research related to the effect of relaxation therapy on reducing anxiety in post-sectio caesarean mothers. The method used in the preparation of a literature review is to search for several articles by searching through nursing journals, science direct, google scholar, Pubmed, and EBSCO. The results of 8 previous research articles showed that relaxation therapy was effective in reducing maternal anxiety levels. Although there are various types of relaxation techniques autogenic relaxation has a medium-high effect size and is recommended for dealing with anxiety compared to other relaxation techniques